Effect of vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients: results of a randomized controlled trial - Libuda, Lars; Timmesfeld, Nina; Antel, Jochen; Hirtz, Raphael; Bauer, Jens; Führer, Dagmar; Zwanziger, Denise; Öztürk, Dana; Langenbach, Gina; Hahn, Denise; Ring, Stefanie; Peters, Triinu; et al. (European Journal of Nutrition)
Abstract Purpose While observational studies revealed inverse associations between serum vitamin D levels [25(OH)D] and depression, randomized controlled trials (RCT) in children and adolescents are lacking. This RCT examined the effect of an untreated vitamin D deficiency compared to an immediate vitamin D 3 supplementation on depression scores in children and adolescents during standard day and in-patient psychiatric treatment. Methods Patients with vitamin D deficiency [25(OH)D ≤ 30 nmol/l] and at least mild depression [Beck Depression Inventory II (BDI-II) > 13] ( n = 113) were 1:1 randomized into verum (VG; 2640 IU vitamin D 3 /d) or placebo group (PG) in a double-blind manner. During the intervention period of 28 days, both groups additionally received treatment as usual. BDI-II scores were assessed as primary outcome, DISYPS-II (Diagnostic System for Mental Disorders in Childhood and Adolescence, Self- and Parent Rating) and serum total 25(OH)D were secondary outcomes. Results At admission, 49.3% of the screened patients ( n = 280) had vitamin D deficiency. Although the intervention led to a higher increase of 25(OH)D levels in the VG than in the PG (treatment difference: + 14 ng/ml; 95% CI 4.86–23.77; p = 0.003), the change in BDI-II scores did not differ (+ 1.3; 95% CI − 2.22 to 4.81; p = 0.466). In contrast, DISYPS parental ratings revealed pronounced improvements of depressive symptoms in the VG (− 0.68; 95% CI − 1.23 to − 0.13; p = 0.016). Conclusion Whereas this study failed to show a vitamin D supplementation effect on self-rated depression in adolescent in- or daycare patients, parents reported less depressive symptoms in VG at the end of our study. Future trials should consider clinician-rated depressive symptoms as primary outcome. Trial registration “German Clinical Trials Register” ( https://www.drks.de ), registration number: DRKS00009758

Evaluation of Metabolic Profiles of Patients with Anorexia Nervosa at Inpatient Admission, Short- and Long-Term Weight Regain—Descriptive and Pattern Analysis - Föcker, Manuel; Cecil, Alexander; Prehn, Cornelia; Adamski, Jerzy; Albrecht, Muriel; Adams, Frederike; Hinney, Anke; Libuda, Lars; Bühlmeier, Judith; Hebebrand, Johannes; Peters, Triinu; Antel, Jochen (Metabolites)
Acute anorexia nervosa (AN) constitutes an extreme physiological state. We aimed to detect state related metabolic alterations during inpatient admission and upon short- and long-term weight regain. In addition, we tested the hypothesis that metabolite concentrations adapt to those of healthy controls (HC) after long-term weight regain. Thirty-five female adolescents with AN and 25 female HC were recruited. Based on a targeted approach 187 metabolite concentrations were detected at inpatient admission (T0), after short-term weight recovery (T1; half of target-weight) and close to target weight (T2). Pattern hunter and time course analysis were performed. The highest number of significant differences in metabolite concentrations (N = 32) were observed between HC and T1. According to the detected main pattern, metabolite concentrations at T2 became more similar to those of HC. The course of single metabolite concentrations (e.g., glutamic acid) revealed different metabolic subtypes within the study sample. Patients with AN after short-term weight regain are in a greater “metabolic imbalance” than at starvation. After long-term weight regain, patients reach a metabolite profile similar to HC. Our results might be confounded by different metabolic subtypes of patients with AN.

Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children’s cognitive function in a randomized crossover study - Jansen, Kathrin; Tempes, Jana; Drozdowska, Alina; Gutmann, Maike; Falkenstein, Michael; Buyken, Anette; Libuda, Lars; Rudolf, Henrik; Lücke, Thomas; Kersting, Mathilde (European Journal of Clinical Nutrition)

Physical activity and health promotion for nursing staff in elderly care: a study protocol for a randomised controlled trial - Otto, Ann-Kathrin; Pietschmann, Juliane; Appelles, Luisa-Marie; Bebenek, Michael; Bischoff, Laura L; Hildebrand, Claudia; Johnen, Bettina; Jöllenbeck, Thomas; Kemmler, Wolfgang; Klotzbier, Thomas; Korbus, Heide; Rudisch, Julian; et al. (BMJ Open)
Introduction Nursing staff is burdened by high workload and stress. Furthermore, heavy lifting, as well as transferring nursing home residents, cause lumbar tissue damage and back pain. Exercise intervention studies to reduce work-related problems are rare and the evidence for efficacy of studies among nurses is limited. Studies including targeted analysis of requirements are necessary to generate effective recommendations and tailored interventions for health promotion programmes. The purpose of this multicentred intervention study is to identify work-related problems, to implement health promotion programmes and to evaluate their effectiveness. Methods and analysis A randomised controlled trial will be conducted, including a total of 48 nursing home facilities in eight regions of Germany with an estimated sample size of 700 nurses. Standardised ergonomics and posture training (10 weeks, once a week for 20–30 min) and subsequently, back-fitness training (12 weeks, once a week for 45–60 min) will be administered. Following the implementation of standardised health promotion programmes, further demand-oriented interventions can be implemented. The perceived exposure to work-related demands, work-related pain in different parts of the body, health-related quality of life, perceived stress, work-related patterns of behaviour and experience, presentism behaviour, work environment as well as general needs and barriers to health promotion, will be assessed at baseline (pre-test), at 10 weeks (post-test, after ergonomics training), at 22 weeks (post-test, after back-fitness training) and at 34 weeks of the programme (follow-up). Ethics and dissemination The study was reviewed and approved by the local ethics committee of the University of Hamburg (AZ: 2018_168). The results of the study will be published in open-access and international journals. Furthermore, the results will be presented in the participating nursing homes and at national and international conferences. Trial registration number DRKS.de (DRKS00015241).
Keywords: General Medicine

1. Sonntag nach Weihnachten 27.12.2020. Lukas 2,(22-24)25-38(39-40): Missionarische Spiritualität - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien III/1)

Kommunale Planung für Senior*innen bis 2025. Fortschreibung des Altenhilfeplans aus dem Jahr 2013

Auswirkungen der digitalen Flexibilisierung des Fertigungsortes auf die Verteilung der Besteuerungsrechte – Ergebnisse von Modellrechnungen zum 3D-Druck-Verfahren - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Psychische Auffälligkeiten bei Kindern und Jugendlichen, für die das Jugendamt in Anspruch genommen wurde - Wagenknecht, Inga; Meier-Gräwe, Uta (Praxis der Kinderpsychologie und Kinderpsychiatrie)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Golf spielen gegen die Vergesslichkeit: Effekte des Erlernens der Sportart auf das Default Mode Netzwerk des Gehirns - Ströhlein, Julia Kristin; Vieluf, Solveig; van den Bongard, Franziska; Gölz, Christian Johannes; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Im Rahmen der Demenz vom Alzheimer-Typ (DAT) zeigt sich eine gestörte neuronale Netzwerkorganisation, welche sich unter anderem auch im Default Mode Netzwerk (DMN) widerspiegelt. Multimodale Interventionen, wie zum Beispiel Golf, können einen positiven Einfluss auf die funktionelle Integrität der Netzwerke haben. Methodik Im Rahmen einer Pilotstudie wurde der Einfluss des Erlernens der Sportart Golf bei sieben älteren Menschen (> 60 Jahre) mit subjektiven Gedächtnisbeschwerden auf die funktionelle Konnektivität des DMN untersucht. Die Probanden haben 22 Wochen unter Anleitung eines professionellen Golftrainers dreimal wöchentlich je 60 min trainiert. Vor (Messzeitpunkt 0, MZP0) und nach der Intervention (Messzeitpunkt 1, MZP1) wurde eine Elektroenzephalografie (EEG)-Messung unter Ruhebedingungen (resting-state) durchgeführt. Die EEG-Daten wurden mit einem Magnetresonanztomographie-Template koregistriert. Die Konnektivitätsanalyse wurde in 15 Regionen des DMN durchgeführt und im Längsschnitt verglichen. Dabei wurden die Frequenzbänder beta (14–29 Hz) und theta (5–7 Hz) berücksichtigt. Ergebnisse Nach der Intervention wurde eine höhere funktionelle Konnektivität im gesamten DMN bei 5 / 7 Teilnehmenden im beta Frequenzband bzw. bei 6 / 7 Probanden im theta Frequenzband zu MZP1 im Vergleich zu MZP0 gemessen. Im anterioren DMN war bei allen Probanden und Probandinnen die funktionelle Konnektivität im beta Frequenzband zu MZP1 im Vergleich zu MZP 0 höher, während sie im theta-Band bei 6 von 7 Teilnehmenden niedriger war. Im posterioren DMN war bei 6 von 7 (beta), bzw. 5 von 7 (theta) Probanden und Probandinnen die funktionelle Konnektivität zu MZP1 höher als zu MZP0. Spearman-Korrelationsanalysen zeigen zudem einen Zusammenhang zwischen der Teilnahmehäufigkeit und der prozentualen Veränderung der funktionellen Konnektivität im gesamten DMN des beta Frequenzbandes (r = 0,786, p = 0,036) und im anterioren DMN des theta Frequenzbandes (r = –0,821, p = 0,023). Fazit Auf Basis der vorliegenden Daten lässt sich vermuten, dass das Erlernen der Sportart Golf einen Einfluss auf das DMN haben könnte. Die Ergebnisse bilden die Grundlage für die Planung einer Studie mit einer größeren Kohorte und randomisierten kontrollierten Design.

Healthy subjects with lax knees use less knee flexion rather than muscle control to limit anterior tibia translation during landing - Keizer, Michèle N. J.; Hijmans, Juha M.; Gokeler, Alli; Benjaminse, Anne; Otten, Egbert (Journal of Experimental Orthopaedics)
Abstract Purpose It has been reported that there is no correlation between anterior tibia translation (ATT) in passive and dynamic situations. Passive ATT (ATTp) may be different to dynamic ATT (ATTd) due to muscle activation patterns. This study aimed to investigate whether muscle activation during jumping can control ATT in healthy participants. Methods ATTp of twenty-one healthy participants was measured using a KT-1000 arthrometer. All participants performed single leg hops for distance during which ATTd, knee flexion angles and knee flexion moments were measured using a 3D motion capture system. During both tests, sEMG signals were recorded. Results A negative correlation was found between ATTp and the maximal ATTd (r = − 0.47, p = 0.028). An N-Way ANOVA showed that larger semitendinosus activity was seen when ATTd was larger, while less biceps femoris activity and rectus femoris activity were seen. Moreover, larger knee extension moment, knee flexion angle and ground reaction force in the anterior-posterior direction were seen when ATTd was larger. Conclusion Participants with more ATTp showed smaller ATTd during jump landing. Muscle activation did not contribute to reduce ATTd during impact of a jump-landing at the observed knee angles. However, subjects with large ATTp landed with less knee flexion and consequently showed less ATTd. The results of this study give information on how healthy people control knee laxity during jump-landing. Level of evidence III
Keywords: Orthopedics and Sports Medicine

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Parameterized complexity of abduction in Schaefer’s framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Journal of Logic and Computation)
Abstract Abductive reasoning is a non-monotonic formalism stemming from the work of Peirce. It describes the process of deriving the most plausible explanations of known facts. Considering the positive version, asking for sets of variables as explanations, we study, besides the problem of wether there exists a set of explanations, two explanation size limited variants of this reasoning problem (less than or equal to, and equal to a given size bound). In this paper, we present a thorough two-dimensional classification of these problems: the first dimension is regarding the parameterized complexity under a wealth of different parameterizations, and the second dimension spans through all possible Boolean fragments of these problems in Schaefer’s constraint satisfaction framework with co-clones (T. J. Schaefer. The complexity of satisfiability problems. In Proceedings of the 10th Annual ACM Symposium on Theory of Computing, May 1–3, 1978, San Diego, California, USA, R.J. Lipton, W.A. Burkhard, W.J. Savitch, E.P. Friedman, A.V. Aho eds, pp. 216–226. ACM, 1978). Thereby, we almost complete the parameterized complexity classification program initiated by Fellows et al. (The parameterized complexity of abduction. In Proceedings of the Twenty-Sixth AAAI Conference on Articial Intelligence, July 22–26, 2012, Toronto, Ontario, Canada, J. Homann, B. Selman eds. AAAI Press, 2012), partially building on the results by Nordh and Zanuttini (What makes propositional abduction tractable. Artificial Intelligence, 172, 1245–1284, 2008). In this process, we outline a fine-grained analysis of the inherent parameterized intractability of these problems and pinpoint their FPT parts. As the standard algebraic approach is not applicable to our problems, we develop an alternative method that makes the algebraic tools partially available again.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

NFDI4Culture - Consortium for research data on material and immaterial cultural heritage - Altenhöner, Reinhard; Blümel, Ina; Boehm, Franziska; Bove, Jens; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Dieckmann, Lisa; Effinger, Maria; Hagener, Malte; Hammes, Andrea; Heller, Lambert; et al. (Research Ideas and Outcomes)
Digital data on tangible and intangible cultural assets is an essential part of daily life, communication and experience. It has a lasting influence on the perception of cultural identity as well as on the interactions between research, the cultural economy and society. Throughout the last three decades, many cultural heritage institutions have contributed a wealth of digital representations of cultural assets (2D digital reproductions of paintings, sheet music, 3D digital models of sculptures, monuments, rooms, buildings), audio-visual data (music, film, stage performances), and procedural research data such as encoding and annotation formats. The long-term preservation and FAIR availability of research data from the cultural heritage domain is fundamentally important, not only for future academic success in the humanities but also for the cultural identity of individuals and society as a whole. Up to now, no coordinated effort for professional research data management on a national level exists in Germany. NFDI4Culture aims to fill this gap and create a user-centered, research-driven infrastructure that will cover a broad range of research domains from musicology, art history and architecture to performance, theatre, film, and media studies. The research landscape addressed by the consortium is characterized by strong institutional differentiation. Research units in the consortium's community of interest comprise university institutes, art colleges, academies, galleries, libraries, archives and museums. This diverse landscape is also characterized by an abundance of research objects, methodologies and a great potential for data-driven research. In a unique effort carried out by the applicant and co-applicants of this proposal and ten academic societies, this community is interconnected for the first time through a federated approach that is ideally suited to the needs of the participating researchers. To promote collaboration within the NFDI, to share knowledge and technology and to provide extensive support for its users have been the guiding principles of the consortium from the beginning and will be at the heart of all workflows and decision-making processes. Thanks to these principles, NFDI4Culture has gathered strong support ranging from individual researchers to high-level cultural heritage organizations such as the UNESCO, the International Council of Museums, the Open Knowledge Foundation and Wikimedia. On this basis, NFDI4Culture will take innovative measures that promote a cultural change towards a more reflective and sustainable handling of research data and at the same time boost qualification and professionalization in data-driven research in the domain of cultural heritage. This will create a long-lasting impact on science, cultural economy and society as a whole.
Keywords: Research Data Management

Analysis of the Characteristic Flow Areas for Erdmenger-Elements to Predict the Throughput-Pressure Behavior of Co-Rotating Twin Screw Extruders by Using 3D FEM Simulation - Schöppner, Volker; Sporkmann, F. (35th International Conference of the Polymer Processing Society (PPS))

Vorausschau und Technologieplanung. 15. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 21. und 22. November 2019 - Gausemeier, Jürgen

Analyse sicherheitskritischer Software für RISC-V Prozessoren - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (MBMV 2019-22.Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2019))
In diesem Artikel stellen wir eine Methode zur nicht-invasiven dynamischen Speicher- und IO-Analyse mit QEMU für sicherheitskritische eingebettete Software für die RISC-V Befehlssatzarchitektur vor. Die Implementierung basiert auf einer Erweiterung des Tiny Code Generator (TCG) des quelloffenen CPU-Emulators QEMU um die dynamische Identifikation von Zugriffen auf Datenspeicher sowie auf an die CPU angeschlossene IO-Geräte. Wir demonstrieren die Funktionalität der Methode anhand eines Versuchsaufbaus, bei dem eine Schließsystemkontrolle mittels serieller UART-Schnittstelle an einen RISC-V-Prozessor angebunden ist. Dieses Szenario zeigt, dass ein unberechtigter Zugriff auf die UART-Schnittstelle frühzeitig aufgedeckt und ein Angriff auf eine Zugangskontrolle somit endeckt werden kann.

Influence of precursor concentration on spray and particle formation in flame spray pyrolysis - Bieber, M.; Tischendorf, R.; Reddemann, M.; Schmid, H.-J.; Kneer, R.
Liquid atomization is expected to be a key process in Flame Spray Pyrolysis, as it determines the primary droplet size and velocity distribution, which represent initial conditions for flame shape and temperature field. A well-defined manipulation of atomization may be achieved by variation of nozzle geometry, injection parameter or fluid properties. However, change of fluid properties, e.g. varying solvents or increasing the precursor concentration, also influences the final particle properties. In this work, the influence of precursor concentration on fluid properties, spray and particle formation in Flame Spray Pyrolysis is experimentally investigated. High-speed shadowgraphy and Phase-Doppler measurements are conducted in a semi-closed combustion chamber with a well-defined burner geometry (SpraySyn burner) that is based on a coaxial atomization principle. By adding precursor to the flammable solvent, resulting spray characteristics, flame shape and appearance are changed in color, shape and mean droplet size distribution. Compared to resulting mean droplet sizes of pure solvent mixtures (D32, 22 μm), mean droplet sizes in the center of the precursor flame at 30 mm above the burner are generally smaller (D32, 18 μm). Persisting high share of small droplets in the droplet size distribution are presented, that presumably origin from an accumulation of metal organic precursor at the droplet surface during combustion, that acts as a diffusive barrier for high volatility solvent and thus reduces droplet evaporation. Sufficiently high above the nozzle exit, increasing the precursor concentration does not affect the radial distribution of mean droplet sizes but leads to increased mean particle sizes. More precursor presumably leads to higher concentrations of prime particles in the flame, thus probability of particle collusion and agglomeration. High-speed imaging at nozzle exit revealed random fluctuations of initial jet diameter, paired with jet axis shifting around 1000 Hz. These superposed fluctuations determine the initial conditions for atomization, induce pulsations in the flame and thus initiate the entire chain of the particle synthesis process.
Keywords: FSP; nanoparticle synthesis; in situ measurements

Age and time trends in sugar intake among children and adolescents: results from the DONALD study - Perrar, Ines; Schmitting, Sarah; Della Corte, Karen W.; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)

Is there a soft drink vs. alcohol seesaw? A cross-sectional analysis of dietary data in the Australian Health Survey 2011–12 - Wong, Tommy H. T.; Buyken, Anette; Brand-Miller, Jennie C.; Louie, Jimmy Chun Yu (European Journal of Nutrition)

Dietary sugars and cardiometabolic risk factors: a network meta-analysis on isocaloric substitution interventions - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)
ABSTRACT Background There is controversy on the relevance of dietary sugar intake for cardiometabolic health. Objective The aim of this network meta-analysis (NMA) was to assess how isocaloric substitutions of dietary sugar with other carbohydrates affect cardiometabolic risk factors, comparing different intervention studies. Methods We included randomized controlled trials (RCTs) investigating the isocaloric effect of substituting dietary sugars (fructose, glucose, sucrose) with other sugars or starch on cardiometabolic risk markers, including LDL cholesterol, triacylglycerol (TG), fasting glucose (FG), glycated hemoglobin (HbA1c), insulin resistance (HOMA-IR), uric acid, C-reactive protein (CRP), alanine transaminase (ALT), aspartate transaminase (AST), and liver fat content. To identify the most beneficial intervention for each outcome, random-effects NMA was conducted by calculating pooled mean differences (MDs) with 95% CIs, and by ranking the surface under the cumulative ranking curves (SUCRAs). The certainty of evidence was evaluated using the Confidence In Network Meta-Analysis tool. Results Thirty-eight RCTs, including 1383 participants, were identified. A reduction in LDL-cholesterol concentrations was shown for the exchange of sucrose with starch (MD: −0.23 mmol/L; 95% CI: −0.38, −0.07 mmol/L) or fructose with starch (MD: −0.22 mmol/L; 95% CI: −0.39, −0.05 mmol/L; SUCRAstarch: 98%). FG concentrations were also lower for the exchange of sucrose with starch (MD: −0.14 mmol/L; 95% CI: −0.29, 0.01 mmol/L; SUCRAstarch: 91%). Replacing fructose with an equivalent energy amount of glucose reduced HOMA-IR (MD: −0.36; 95% CI: −0.71, −0.02; SUCRAglucose: 74%) and uric acid (MD: −23.77 µmol/L; 95% CI: −44.21, −3.32 µmol/L; SUCRAglucose: 93%). The certainty of evidence was rated very low to moderate. No significant effects were observed for TG, HbA1c, CRP, ALT, and AST. Conclusions Our findings indicate that substitution of sucrose and fructose with starch yielded lower LDL cholesterol. Insulin resistance and uric acid concentrations were beneficially affected by replacement of fructose with glucose. Our findings are limited by the very low to moderate certainty of evidence. This review was registered at www.crd.york.ac.uk/prospero as CRD42018080297.

Time and Age Trends in Free Sugar Intake from Food Groups among Children and Adolescents between 1985 and 2016 - Perrar, Ines; Schadow, Alena M.; Schmitting, Sarah; Buyken, Anette; Alexy, Ute (Nutrients)
Trend analyses suggest that free sugar (FS) intake—while still exceeding 10%E—has decreased among German children and adolescents since 2005, yet that intakes may shift from sugars naturally occurring in foods to added sugars as children age. Thus, we analysed time and age trends in FS intake (%E) from food groups among 3–18 year-olds (1985–2016) using 10,761 3-day dietary records from 1312 DONALD participants (660 boys, 652 girls) by use of polynomial mixed-effects regression models. Among girls, FS from sugar & sweets decreased from 1985 to 2016 (linear trend p < 0.0001), but not among boys (p > 0.05). In the total sample, FS intake from juices increased until 2000 and decreased since 2005 (linear, quadratic trend p < 0.0001). FS from sugar sweetened beverages (SSB) decreased non-linearly from 1985 to 2016 (girls: linear, quadratic, cubic trend p < 0.0001; boys: linear, quadratic, cubic trend p < 0.02). Younger children consumed more FS from juices than older ones, who had a higher FS intake from SSB. FS intake from sugar & sweets increased until early adolescence and decreased afterwards. Since sugar & sweets represent the main source of FS intake and the source with the least pronounced decline in intake, public health measures should focus on these products.

Assessing causal links between metabolic traits, inflammation and schizophrenia: a univariable and multivariable, bidirectional Mendelian-randomization study - Lin, Bochao D; Alkema, Anne; Peters, Triinu; Zinkstok, Janneke; Libuda, Lars; Hebebrand, Johannes; Antel, Jochen; Hinney, Anke; Cahn, Wiepke; Adan, Roger; Luykx, Jurjen J (International Journal of Epidemiology)
Abstract Background Blood immunoreactive biomarkers, such as C-reactive protein (CRP), and metabolic abnormalities have been associated with schizophrenia. Studies comprehensively and bidirectionally probing possible causal links between such blood constituents and liability to schizophrenia are lacking. Methods To disentangle putative causal links between CRP blood levels and schizophrenia in both directions, we conducted multiple univariable Mendelian-randomization (MR) analyses, ranging from fixed-effect to inverse variance-weighted (IVW), weighted-median, MR Egger and generalized summary-data-based Mendelian-randomization (GSMR) models. To prioritize metabolic risk factors for schizophrenia, a novel multivariable approach was applied: multivariable Mendelian-randomization–Bayesian model averaging (MR-BMA). Results All forward univariable MR analyses consistently showed that CRP has a protective effect on schizophrenia, whereas reverse MR analyses consistently suggested absent causal effects of schizophrenia liability on CRP blood levels. Using MR-BMA, as the top protective factors for schizophrenia we prioritized leucine and as the prime risk-factor triglycerides in medium very-low-density lipoprotein (VLDL). The five best-performing MR-BMA models provided one additional risk factor: triglycerides in large VLDL; and two additional protective factors: citrate and lactate. Conclusions Our results add to a growing body of literature hinting at metabolic changes—in particular of triglycerides—independently of medication status in schizophrenia. We also highlight the absent effects of genetic liability to schizophrenia on CRP levels.

Effects of LC-PUFA supply via complementary food on infant development—a food based intervention (RCT) embedded in a total diet concept - Kalhoff, Hermann; Mesch, Christina M.; Stimming, Madlen; Israel, Andreas; Spitzer, Christoph; Beganovic, Latifa; Perez, Rocio Estella; Koletzko, Berthold; Warschburger, Petra; Kersting, Mathilde; Libuda, Lars (European Journal of Clinical Nutrition)

Verbraucherbildung als Bildung für Lebensführung - Schlegel-Matthies, Kirsten (Verbraucherbildung: Ein weiter Weg zum mündigen Verbraucher)

Haushaltsbezogene Bildung – quo vadis? Daseinsvorsorge und Lebensführung im Wandel - Schlegel-Matthies, Kirsten (Haushalt in Bildung & Forschung)
Der Beitrag geht der Frage nach, wie haushaltsbezogene Bildung als Ernährungs- und Verbraucherbildung umgesetzt werden kann, damit Jugendliche selbstbestimmt und verantwortlich ihre individuellen Vorstellungen von einem „guten“ und „gelingenden“ Leben umsetzen können. Die Auseinandersetzung mit dem Zusammenwirken von gesellschaftlicher Lebensweise, privater Lebensführung und individuellen Lebensstilen erweist sich dabei als bedeutsam.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: A Systematic Review and Updated Meta-Analyses of Prospective Cohort Studies - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
Published meta-analyses indicate significant but inconsistent incident type-2 diabetes (T2D)-dietary glycemic index (GI) and glycemic load (GL) risk ratios or risk relations (RR). It is now over a decade ago that a published meta-analysis used a predefined standard to identify valid studies. Considering valid studies only, and using random effects dose–response meta-analysis (DRM) while withdrawing spurious results (p < 0.05), we ascertained whether these relations would support nutrition guidance, specifically for an RR > 1.20 with a lower 95% confidence limit >1.10 across typical intakes (approximately 10th to 90th percentiles of population intakes). The combined T2D–GI RR was 1.27 (1.15–1.40) (p < 0.001, n = 10 studies) per 10 units GI, while that for the T2D–GL RR was 1.26 (1.15–1.37) (p < 0.001, n = 15) per 80 g/d GL in a 2000 kcal (8400 kJ) diet. The corresponding global DRM using restricted cubic splines were 1.87 (1.56–2.25) (p < 0.001, n = 10) and 1.89 (1.66–2.16) (p < 0.001, n = 15) from 47.6 to 76.1 units GI and 73 to 257 g/d GL in a 2000 kcal diet, respectively. In conclusion, among adults initially in good health, diets higher in GI or GL were robustly associated with incident T2D. Together with mechanistic and other data, this supports that consideration should be given to these dietary risk factors in nutrition advice. Concerning the public health relevance at the global level, our evidence indicates that GI and GL are substantial food markers predicting the development of T2D worldwide, for persons of European ancestry and of East Asian ancestry.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: Assessment of Causal Relations - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
While dietary factors are important modifiable risk factors for type 2 diabetes (T2D), the causal role of carbohydrate quality in nutrition remains controversial. Dietary glycemic index (GI) and glycemic load (GL) have been examined in relation to the risk of T2D in multiple prospective cohort studies. Previous meta-analyses indicate significant relations but consideration of causality has been minimal. Here, the results of our recent meta-analyses of prospective cohort studies of 4 to 26-y follow-up are interpreted in the context of the nine Bradford-Hill criteria for causality, that is: (1) Strength of Association, (2) Consistency, (3) Specificity, (4) Temporality, (5) Biological Gradient, (6) Plausibility, (7) Experimental evidence, (8) Analogy, and (9) Coherence. These criteria necessitated referral to a body of literature wider than prospective cohort studies alone, especially in criteria 6 to 9. In this analysis, all nine of the Hill’s criteria were met for GI and GL indicating that we can be confident of a role for GI and GL as causal factors contributing to incident T2D. In addition, neither dietary fiber nor cereal fiber nor wholegrain were found to be reliable or effective surrogate measures of GI or GL. Finally, our cost–benefit analysis suggests food and nutrition advice favors lower GI or GL and would produce significant potential cost savings in national healthcare budgets. The high confidence in causal associations for incident T2D is sufficient to consider inclusion of GI and GL in food and nutrient-based recommendations.

Developmental trajectories of body mass index from childhood into late adolescence and subsequent late adolescence–young adulthood cardiometabolic risk markers - Oluwagbemigun, Kolade; Buyken, Anette; Alexy, Ute; Schmid, Matthias; Herder, Christian; Nöthlings, Ute (Cardiovascular Diabetology)

DNA origami directed 3D nanoparticle superlattice via electrostatic assembly. - Julin, S; Korpi, A; Shen, B; Liljeström, V; Ikkala, O; Keller, Adrian; Linko, V; Kostiainen, MA (Nanoscale)

Typisierung und Strukturierung digitaler Plattformen im Kontext Business-to-Business - Wortmann, Fabio; Ellermann, Kai Fabian; Kühn, Arno; Dumitrescu, Roman (Vorausschau und Technologieplanung, 15. Symposium für Vorausschau und Technologieplanung, 21.-22. November 2019, Berlin)

The 31st ACM Symposium on Parallelism in Algorithms and Architectures, SPAA 2019, Phoenix, AZ, USA, June 22-24, 2019

Analyse der Veränderung der zwischenstaatlichen Gewinnaufteilung bei Einführung einer standardisierten Gewinnverteilungsmethode am Beispiel des Einsatzes von 3D-Druckern - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren

Rendering of Complex Heterogenous Scenes using Progressive Blue Surfels - Brandt, Sascha; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (arXiv:1904.08225)
We present a technique for rendering highly complex 3D scenes in real-time by generating uniformly distributed points on the scene's visible surfaces. The technique is applicable to a wide range of scene types, like scenes directly based on complex and detailed CAD data consisting of billions of polygons (in contrast to scenes handcrafted solely for visualization). This allows to visualize such scenes smoothly even in VR on a HMD with good image quality, while maintaining the necessary frame-rates. In contrast to other point based rendering methods, we place points in an approximated blue noise distribution only on visible surfaces and store them in a highly GPU efficient data structure, allowing to progressively refine the number of rendered points to maximize the image quality for a given target frame rate. Our evaluation shows that scenes consisting of a high amount of polygons can be rendered with interactive frame rates with good visual quality on standard hardware.

Numerical Simulation of Forced Convection in a Microchannel with Realistic Roughness of 3D Printed Surface - Manavi, Seyed Alborz; Kenig, Eugeny (Computer Aided Chemical Engineering)

Combining Verifiers in Conditional Model Checking via Reducers - Beyer, Dirk; Jakobs, Marie-Christine; Lemberger, Thomas; Wehrheim, Heike (Software Engineering and Software Management (SE/SWM 2019), Stuttgart, Germany, February 18-22, 2019)

Testing Balancedness of ML Algorithms - Sharma, Arnab; Wehrheim, Heike (Software Engineering and Software Management, {SE/SWM} 2019, Stuttgart, Germany, February 18-22, 2019)

Plastic droplet welding: bond strength between plastic freeforming structures and continuous fiber-reinforced thermoplastic composites - Moritzer, Elmar; Hirsch, André; Heim, H.P.; Cherif, C.; Truemper, W. (Welding in the World)
Plastic freeforming (PF) is an additive-manufacturing process for producing three-dimensional plastic parts based on 3D CAD data by applying plastic droplets in layers. This process is used to produce customer-specific and complex geometries (prototypes and small series) on organic sheets. A comparable serial process is the injection of a second component onto organic sheets by injection molding. A sufficient bond between the PF structure and the organic sheets is of particular importance for each application. If this is not guaranteed, the composite system cannot withstand the mechanical load and fails. The force exerted on the system can no longer be transmitted between the PF structure and the organic sheet. The organic sheet is made of glass fiber-reinforced polypropylene (PP). The connection between the organic sheet and the PF structure is achieved by welding the molten polymer droplets and the surface of the organic sheet. The PF structures are made of PP to ensure sufficient compatibility with regard to the weldability of the components. The processing of PP in the PF process is a challenge because PP is a semicrystalline material. The shrinkage of semi-crystalline materials is significantly higher compared to amorphous materials. Due to the layered structure of the components, the shrinkage of the individual layers results in undesired warpage. The adhesive strength between the organic sheet and the PF structure is investigated by determining the bending strength in the 3-point bending test. The investigations include an optimization of the process parameters to maximize the adhesive strength. The experimental investigations show that an increase of the nozzle and build chamber temperature leads to a higher adhesive strength. In further investigations, the temperature of the nozzle shows no significant influence on the surface temperature despite the expected heat radiation. The surface temperature is almost only dependent on the temperature of the build chamber.

Vitamin D and the Risk of Depression: A Causal Relationship? Findings from a Mendelian Randomization Study - Libuda, Lars; Laabs, Björn-Hergen; Ludwig, Christine; Bühlmeier, Judith; Antel, Jochen; Hinney, Anke; Naaresh, Roaa; Föcker, Manuel; Hebebrand, Johannes; König, Inke R.; Peters, Triinu (Nutrients)
While observational studies show an association between 25(OH)vitamin D concentrations and depressive symptoms, intervention studies, which examine the preventive effects of vitamin D supplementation on the development of depression, are lacking. To estimate the role of lowered 25(OH)vitamin D concentrations in the etiology of depressive disorders, we conducted a two-sample Mendelian randomization (MR) study on depression, i.e., “depressive symptoms” (DS, n = 161,460) and “broad depression” (BD, n = 113,769 cases and 208,811 controls). Six single nucleotide polymorphisms (SNPs), which were genome-wide significantly associated with 25(OH)vitamin D concentrations in 79,366 subjects from the SUNLIGHT genome-wide association study (GWAS), were used as an instrumental variable. None of the six SNPs was associated with DS or BD (all p > 0.05). MR analysis revealed no causal effects of 25(OH)vitamin D concentration, either on DS (inverse variance weighted (IVW); b = 0.025, SE = 0.038, p = 0.52) or on BD (IVW; b = 0.020, SE = 0.012, p = 0.10). Sensitivity analyses confirmed that 25(OH)vitamin D concentrations were not significantly associated with DS or BD. The findings from this MR study indicate no causal relationship between vitamin D concentrations and depressive symptoms, or broad depression. Conflicting findings from observational studies might have resulted from residual confounding or reverse causation.

Risk factors for a low weight gain in the early stage of adolescent anorexia nervosa inpatient treatment: findings from a pilot study - Knoll-Pientka, Nadja; Bühlmeier, Judith; Peters, Triinu; Albrecht, Muriel; Adams, Frederike; Wustrau, Katharina; Teufel, Martin; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity)

Clinical Trials Required to Assess Potential Benefits and Side Effects of Treatment of Patients With Anorexia Nervosa With Recombinant Human Leptin - Hebebrand, Johannes; Milos, Gabriella; Wabitsch, Martin; Teufel, Martin; Führer, Dagmar; Bühlmeier, Judith; Libuda, Lars; Ludwig, Christine; Antel, Jochen (Frontiers in Psychology)

Mit 3D-Druck umfassende Teilhabe möglich machen - Kruse, Anne; Mummert, Michael (Werkstatt:Dialog)

Posterbeitrag: Didaktisches Konzept und Prototyp eines auf Augmented Reality basierenden virtuellen Vorpraktikums in der Elektrotechnik - Alptekin, Mesut; Temmen, Katrin
Es existieren bisher zahlreiche Studien, die das Potenzial von Augmented Reality (AR) in verschiedenen Bildungsbereichen und seine Auswirkungen auf die Lernenden hinsichtlich ihrer erhöhten Motivation, verbesserter Lernfähigkeit, Konzentration auf das Thema usw. hervorheben. Dabei eignen sich AR-Anwendungen sowohl für den Einsatz in formellen, als auch informellen Lernumgebungen und Bildungsinstitutionen, beginnend mit Kunstkursen in Vorschulen über Biologie, Geschichte, Chemie, Physik etc. in weiterführenden Schulen und Universitäten [1]. Trotz der steigenden Zahl an Studien liegen nur wenigen AR-Anwendungen ein geeignetes didaktisches Konzept zu Grunde. Ferner fehlen allgemeine Studien, die die lernfördernden Eigenschaften von AR im Bereich der Vorbereitung und Begleitung von Laborpraktika untersuchen. Aktuelle Anwendungen erweitern lediglich gedruckte Lerninhalte mit zusätzlichen Links, Videos oder statischen 3D-Modellen oder benötigen spezielle Voraussetzung für die Nutzung der AR-Anwendung [2]. Der vorliegende Beitrag untersucht und konzentriert sich daher auf ein didaktisches Konzept für eine auf mobilen Geräten basierende AR-Anwendung (App) zum Erwerb und zur Vertiefung praktischer Fertigkeiten im Umgang mit elektrotechnischen Laborgeräten und -komponenten. In einer früheren Arbeit wurden die Möglichkeiten und Grenzen der AR-Technologie in der Ingenieurausbildung mit besonderem Fokus auf Laborarbeit untersucht, um häufige Fehler im Designkonzept zu vermeiden. Das didaktische Grundkonzept beruht auf dem „Constructive Alignement“ nach Biggs [3] mit der Definition der drei obligatorischen Schritte: Lernziele, Lehr- / Lernaktivitäten und Prüfungsmethoden. Die Lernziele werden – angelehnt an die modifizierte Bloom-Taxonomie nach Anderson und Krathwohl [4] – weiter konkretisiert, woraus dann im weiteren Schritt mögliche Lehrszenarien in AR gestaltet wurden.
Keywords: Augmented Reality; Laborpraktikum; didaktische Konzepte; Constructive Alignment

Deep eutectic solvents as active media for the preparation of highly conducting 3D free-standing PANI xerogels and their derived N-doped and N-, P-codoped porous carbons - Sánchez-Leija, R.J.; Lopez Salas, Nieves; Fierro, J.L.G.; Gutiérrez, M.C.; Ferrer, M.L.; Mota-Morales, J.D.; Luna-Bárcenas, G.; Monte, F. del (Carbon)
Keywords: General Chemistry; General Materials Science

Anisotropic Water-Mediated Proton Conductivity in Large Iron(II) Metal–Organic Framework Single Crystals for Proton-Exchange Membrane Fuel Cells - Bunzen, Hana; Javed, Ali; Klawinski, Danielle; Lamp, Anton; Grzywa, Maciej; Kalytta-Mewes, Andreas; Tiemann, Michael; von Nidda, Hans-Albrecht Krug; Wagner, Thorsten; Volkmer, Dirk (ACS Applied Nano Materials)
Herein we present a new proton-conducting iron(II) metal–organic framework (MOF) of an unusual structure formed by chains of alternating bistriazolate-p-benzoquinone anions and iron(II) cations with four axially coordinated water molecules. These chains assemble via π–π stacking between the aromatic units to form a three-dimensional grid-like network with channel pores filled with water molecules. The material was structurally characterized by single-crystal XRD analysis, and its water and thermal stability was investigated. The proton conductivity was studied by impedance measurements on needle-like single crystals. A simple but efficient measurement setup consisting of interdigital electrodes was used. The influence of the crystal orientation, temperature, and humidity was investigated. The iron(II)-MOF showed the highest proton conductivity of 3.3·10–3 S cm–1 at 22 °C and 94% relative humidity. Contrary to most known structures, the conductivity in this material is controlled by chemical properties of the pore system rather than by grain boundaries. The presented material is the starting point for further tailoring the proton-conducting properties, independent of morphological features which could find potential applications as membrane materials in proton-exchange membrane fuel cells.

Subcycle Wannier-Stark Localization by Mid-Infrared Bias in Gallium Arsenide - Meier, Torsten; Bühler, Johannes; Schmidt, Christian; Heinrich, Alexander-Cornelius; Allerbeck, Jonas; Podzimski, Reinold; Berghoff, Daniel; Schmidt, Wolf Gero; Reichl, Christian; Wegscheider, Werner; Brida, Daniele; Leitenstorfer, Alfred (XXI International Conference on Ultrafast Phenomena 2018 (UP 2018))
The fundamental interband absorption in gallium arsenide shows a strong blue shift when biased by mid-infrared transients exceeding 10 MV/cm. This subcycle feature is induced by the localization of electronic wavefunctions from 3D to 2D.

Guidelines for post processing oriented design of additive manufactured parts for use in topology optimization - Lammers, Stefan; Tominski, Johannes; Zimmer, Detmar (II International Conference on Simulation for Additive Manufacturing Sim-AM 2019 11-13 September, 2019)
According to ISO / ASTM 52900, additive manufacturing (AM) is defined as "the process of joining materials to make parts from 3D model data, usually layer upon layer, as opposed to conventional manufacturing including subtractive manufacturing technologies and formative manufacturing methodologies” [1]. This results in significant advantages over conventional manufacturing methodologies, such as the production of topologically optimized, complex structures, lower material consumption or shorter product development cycles. In order to be able to use these advantages, the possibilities and restrictions of the processes must be known. In particular, selective laser beam melting (SLM), in which a powdery metallic starting material is melted by means of a laser, requires a sound understanding of the process. For this purpose, design guidelines have been presented in various scientific papers. These design guidelines help to design a component in such a way that it can be manufactured successfully using additive manufacturing. These so-called “AMsuitable design guidelines” can be found among others at Adam, Kranz and Thomas [2,3,4,5]. In contrast to established manufacturing processes, the post-processing of additive components is divided into two steps. First, the AM immanent post processing, such as the removing of the component from the building platform or the removing of the remaining powder. These post-processing steps are in the following referred to “post-processing”. Secondly, the subsequent post-processing steps to improve the component properties, such as milling and turning or a stress-relief annealing. These are referred to as “finishing” and form the focus of this paper. With regard to a successful finishing of additively manufactured components, design guidelines must be taken into account that consider the finishing inherent restrictions and possibilities. In the following, these design guidelines are referred to “finishing suitable”. They can deviate significantly from those of conventionally manufactured components in the case of additively manufactured components. Although there are some investigations that deal with the post-processing of additively manufactured components [6,7], there are hardly any design guidelines that are suitable for finishing [8]. Therefore, knowledge about the finishing of additively manufactured components is based on experimental experience rather than on scientific knowledge. For this reason, design guidelines for a finishing suitable design must be methodically determined and quantified. These quantified design guidelines can be used for an automated design check on complex components like topology optimized geometries.

Toward 3D Integrated Photonics Including Lithium Niobate Thin Films: A Bridge Between Electronics, Radio Frequency, and Optical Technology - Rüsing, Michael; Weigel, Peter O.; Zhao, Jie; Mookherjea, Shayan (IEEE Nanotechnology Magazine)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering

Prinzipien und Strategien der Textgliederung in den Zeitungen des 18. Jahrhunderts – Eine computerbasierte Korpusanalyse - Wille, Manuel (Textgliederungsprinzipien. Ihre Kennzeichnungsformen und Funktionen vom 8. bis 18. Jahrhundert. Akten zum Internationalen Kongress vom 22. bis 24. Juni 2017 an der Universität St. Petersburg)

Textgliederungsprinzipien und Beziehungsgestaltung im Stammbuch von 1559–1878 - Schuster, Britt-Marie (Textgliederungsprinzipien. Ihre Kennzeichnungsformen und Funktionen in Texten vom 8. bis 18. Jahrhundert. Akten zum Internationalen Kongress an der Staatlichen Universität St. Petersburg vom 22. bis 24. Juni 2017)
Keywords: Textsortengeschichte

Unterstützung des Lernens für kritische Situationen: Potenzial von Augmented Reality für die Instandsetzung auf See - Gräßler, Iris; Pottebaum, Jens; Taplick, Patrick; Roesmann, Daniel; Preuß, Daniel (Go-3D 2019 "Mit 3D Richtung Maritim 4.0" - Tagungsband zur Konferenz Go-3D 2019)
Die Instandsetzung von sicherheitskritischen Komponenten durch Besatzungsmitglieder auf See erfordert technische und organisa-torische Unterstützungsmaßnahmen. Zur Instandsetzung kritischer Systeme auf See bietet AR-Technologie erkennbare Potenziale (Räumliche Visualisierung, Kontextualisierung). Zugleich sollen Instandsetzungs-Einsätze im Sinne des informellen arbeits- und einsatzbezogenen Lernens zum Kompetenzerwerb genutzt werden. Dazu wird eine AR-Architektur vorgestellt, die das Lernen im Anwendungsfall ‚Instandsetzung‘ integriert.